Membongkar Keterlibatan Pejabat-Pejabat AS dalam Serangan 9/11 - Dewi, Rosita (Jurnal Penelitian Politik, 2005)
The attacks of September ll'h, 2001 (9/11) have often compared with the attacks of Pearl Harbor because the American response to 9/11 attacks is similar with American response to Pearl Harbor. But actually these comparison is unjustified, because both events are in different conditions, and the attacks of 9/11 seems to be deliberated event. Because so many evidence pointed out to complicity ofthe US official in 9/11 attacks. There are at least eight possibilities ofthe US official complicity. These possibilities can be understood in many way s, several of them did not involved and several of them are involved in active planning.